PENERAPAN TEKNIK PERNAFASAN BUTEYKO TERHADAP PERUBAHAN HEMODINAMIKA PADA PASIEN ASMA BRONKIAL DI INSTALASI GAWAT DARURAT RSUD KARAWANG - Fauzi. R, Wirdan; Sherly, Sherly (Ensiklopedia of Journal, 2023)
Asthma is a chronic inflammation of the airways. The breathing technique developed to control asthma is the Buyteko breathing technique. The aim of this training is to determine the effectiveness of the Buteyko breathing technique for controlling asthma. This training was carried out in the inpatient..Asthma is a chronic inflammation of the airways caused by airway hyperresponsiveness, mucosal edema and excess mucus production. This inflammation usually recurs with signs of an asthma episode such as coughing, chest tightness, wheezing and dyspnea (Smeltzer, Suzanne C. O'Connell., Bare, 2018). This disease can result in a decrease in the amount of air that can be induced by smooth muscle contractions, thickening of the airway walls and the presence of excess secretions in the airways which are the result of an exaggerated response to allergens. (Jeffrey MC, 2018). Allergy is the strongest predisposing factor for the incidence of asthma, prolonged exposure to airway irritants or allergens also increases the risk of developing asthma. Meanwhile, precipitating factors for asthma symptoms and exacerbations in asthma patients include airway irritants, exercise, stress or deep sadness, sinusitis with postnasal drip, medication therapy, respiratory tract infections caused by viruses and gastroesophageal reflux (Smeltzer, Suzanne C. O' Connell., Bare, 2018)Keywords : buteyko breathing technique, asthma control